A promoter for the first nine genes of the Escherichia coli mra cluster of cell division and cell envelope biosynthesis genes, including ftsI and ftsW. - Hara, H (1997)
We constructed a null allele of the ftsI gene encoding penicillin-binding protein 3 of Escherichia coli. It caused blockage of septation and loss of viability when expression of an extrachromosomal copy of ftsI was repressed, providing a final proof that ftsI is an essential cell division gene. In order to complement this null allele, the ftsI gene cloned on a single-copy mini-F plasmid required a region 1.9 kb upstream, which was found to contain a promoter sequence that could direct expression of a promoterless lacZ gene on a mini-F plasmid. This promoter sequence lies at the beginning of the mra cluster in the 2 min region of the E. coli chromosome, a cluster of 16 genes which, except for the first 2, are known to be involved in cell division and cell envelope biosynthesis. Disruption of this promoter, named the mra promoter, on the chromosome by inserting the lac promoter led to cell lysis in the absence of a lac inducer. The defect was complemented by a plasmid carrying a chromosomal fragment ranging from the mra promoter to ftsW, the fifth gene downstream of ftsI, but not by a plasmid lacking ftsW. Although several potential promoter sequences in this region of the mra cluster have been reported, we conclude that the promoter identified in this study is required for the first nine genes of the cluster to be fully expressed.